The effect of plant growth regulators and urea on physico- chemical parameters of custard apple (Annona squamosa L.) cv. Sindhan (Indian Journal of Arid Horticulture, 2025)
The experiment was conducted to maximize of yield with good quality of fruits in custard apple at Horticulture Instructional farm, Department of Horticulture, Chimanbhai Patel College of Agriculture, Sardarkrushinagar Dantiwada Agri- cultural University, Sardarkrushinagar, Dist. Banaskantha, Gujarat during the year 2005 and 2006. The experiment involved fourteen treatments comprising of three levels each of NAA and GA, (50 ppm, 100 ppm and 150 ppm) and their combinations with 2% Urea, 2% Urea alone and Control. Seventeen year old custard apple plants of uniform growth and size were selected. Plants were planted at distance of 6 m x 6 m. The experiment was laid out in Randomized Block Design (RBD) with three replications. The combined effect of GA, ppm Urea 2% recorded significantly maximum fruit volume (208.33 ml), pulp weight (122.03 g). pulp: peel ratio (1.78), total soluble solids (27.67%), reducing sugars (18.93%), non-reducing sugars (3.91 %) and total sugars (22.87%) while significantly minimum number of seeds per fruit (29.21), peel weight (69.07g) and titrable acidity (0.081 %) as compared to control and all other treatments. The combined effect of GA, ppm + Urea 2 % proved to the best treatment for the improvement of fruit quality of custard apple.
Keywords: comprising; Block Design; seeds; experiment